EFFECTIVE METHODS FOR MEMORIZING NEW WORDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
One of the main challenges faced by language learners is memorizing new words. The reason is that many learners still rely on outdated and ineffective methods. However, in today’s developed world, solutions to this problem have been found. Currently, there are various effective techniques for quickly and easily memorizing foreign words. This article addresses this issue and provides a comprehensive analysis of possible solutions.